Effects of different levels of TDZ, BAP and NAA on the growth of Phalaenopsis violacea using new Dogashima medium - Marliana Topa. (2010., 2010)
Orchids are extraordinarily beautiful and wondrous flowering plants. Phalaenopsis cultivars are epiphyte orchids that are grown throughout the world as potted plants or for cut flowers. Phalaenopsis is one of the most important orchids in commercial markets. This study was carried out to determine to the effects of auxin, naphthalene acetic acid (NAA) and cytokinins ,thidiazuron (TDZ) and benzylaminopurine (BAP) on the growth of Phal.violacea explants and also to identify the best treatment combinations for the growth of Phal.violacea explants. The explants of this experiment were whole blade of Phal.violacea leaves. These explants was cultured in New Dogashima Medium supplemented with different levels (0,1,5 mg 1-1) of TDZ, (0,1,5 mg 1-1) of BAP and ( 0,0.1,0.5 mg 1-1) of NAA. 11 treatments were conducted and this experiment was arranged in a Randomized Completely Block Design (RCBD) with 10 replications. Parameters taken from this study include fresh weight of the explants, number of shoots and PLBs, percentage of contaminations and percentage of dead explants. Subculturing was done every two month. Data collected after six month was analyzed by using Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT) was employed for comparison between means. There were no significant differences on the fresh weight of explants after 8th, 16 and 24th week after culture between all treatments. Longer period of observation is required which is more than six month in order to get better response between all treatments, and then only the best combination of treatment could be determined.
Project paper (B.Agric.Sc.) - Universiti Putra Malaysia, 2010.